Nanoparticle Albumin-Bound-Paclitaxel in the Treatment of Metastatic Urethral Adenocarcinoma: The Significance of Molecular Profiling and Targeted Therapy - Yasmin M. Abaza; Carlos Alemany (Case Reports in Urology)
Primary urethral cancer is rare and accounts for only 0.003% of all malignancies arising from the female genitourinary tract. Due to the rarity of this disease, no consensus exists regarding the optimal therapeutic approach. Nanoparticle albumin-bound-paclitaxel has been shown to be effective in the treatment of a number of malignancies including metastatic breast, pancreatic, and bladder cancer. We present a 67-year-old woman with advanced metastatic urethral adenocarcinoma resistant to two lines of chemotherapy (ifosfamide/paclitaxel/cisplatin and irinotecan/5-fluorouracil/leucovorin) that showed a dramatic response to nanoparticle albumin-bound-paclitaxel. This is the first case report to document the use and efficacy of nanoparticle albumin-bound-paclitaxel in the treatment of unresectable metastatic urethral cancer.